Effectiveness of customer retention strategies in enhancing brand loyalty: A case of FAVCO Company. - Ruwende, Tatenda (Midlands State University, 2017)
The research sought to assess the effectiveness of customer retention strategies in enhancing brand loyalty at FAVCO. The first objective of this research study was to evaluate the effectiveness of customer retention strategies in enhancing brand loyalty at FAVCO. Secondly, it was to determine factors contributing to customer dissatisfaction at FAVCO and lastly to establish benefits contributed by customer retention at FAVCO. The research made an assumption that major factors contributing to brand loyalty were customer retention strategies. For the past 2 years, FAVCO has been facing the problem of corporate customers switching some of their brand choices to competitors like Selby, Valley Fresh and Interfresh. This forced the company to engage into expensive strategies which included price markdown and new customer acquisition. The company in early 2012 invested in customer retention strategies which included customer service, communication, total quality management and complaint management to fight the challenge but the company failed to make corporate customers loyal to the FAVCO brand. The researcher used case study research design and the case studies used were both exploratory and descriptive case studies. Probability sampling method (cluster sampling) and non-probability methods (convenient and judgemental) were used. The researcher used a sample of 28 respondents from corporate customers, management and employees. Data collection was done through interviews with the Sales, FMCG and the Quality control manager as well as questionnaires which were distributed to employees and corporate customers. The research found out that customer retention strategies had strong impact on brand loyalty but more attention was needed in improving them to effectively retain customers and making them loyal to the FAVCO brand. The major recommendations were that FAVCO should not only acquire new customers but rather retain its existing key customers. Further to this, FAVCO should consider also internal marketing, key account management and service recovery as other customer retention strategies that enhance brand loyalty. Finally, FAVCO management was recommended to practice cross departmental participation in planning and improving the retention process to make sure that everyone in the organisation is involved in the customer retention process.